Forty Years of Distance Education: Challenges and implications at the Open University of Sri Lanka - Buddhini Gayathri Jayatilleke; Geetha Udayanganie Kulasekera (Open Praxis, 2020)
Commencing its activities in 1980, the Open University of Sri Lanka (OUSL) has expanded over the years embracing emerging technologies periodically, undergoing a series of technological adoptions gradually through Generations of Distance Education (GDE). The aim of this study is to assess the current status of OUSL, based on Taylor’s conceptual framework of GDE, identify the challenges faced during these technological transformations, and how those challenges were mitigated during its forty years of existence as a single-mode national open and distance learning university in Sri Lanka. This study employs a qualitative research design based on reflective practices of the researchers, narrative accounts of past decision makers, reflections of academics and administrators, and cross-referenced with documentary evidences. The findings show how the OUSL has advanced towards the fifth GDE, amidst challenges and finally propose mitigation strategies that would be useful for future technological interventions.